DESIGNING DIGITAL CONTROLLERS FOR A CONTROLLED PLANT - A. Khaimuldin (Astana IT University, 2020)
This paper report contains an explanation of how to design a digital controller using the Laplace Transform to z-Transform conversion method. The objectives are that the controlled system should track step input with a reasonably small steady-state error and a settling time faster than the open-loop settling time. Furthermore, it should do so with the minimum overshoot that is reasonably possible. The main contribution is to establish the feasibility and ease of the systematic design procedure and future work will focus in more detail on applying the Sampling Theorem and deadbeat controller. There are several objectives that the controlled system should reach: 1. Track step input with a reasonably small steady-state error and a settling time which should be faster than the open-loop settling time. 2. Gain a small overshoot that is sufficiently possible. 3. Have a systematic design procedure. A method for finding the parameters of the deadbeat controller in the MatLab environment is presented. Based on the results obtained the simulation reveals that even when the control grows by one-step, the settling time of the system response could be less than that of the deadbeat controller. The work shows that deadbeat could be a powerful analysis tool since it is possible to grab the entire dynamic easily using several samples. Keywords: z-transform, Sampling Theorem, deadbeat.